The concept map : a tool for learning science concepts and understanding cognitive processes of pre-service teachers - a case study - Wong, Mary Siew Lian (1997)
This case study focused on the concept map as a tool for learning science concepts and understanding cognitive processes of pre-service science teachers. Ninety-nine pre service science teachers from Batu Lintang Teachers's College, Kuching, participated in this study. A comparison of subjects' performance in the pre- and posttreatment achievement tests showed that subjects who were taught science concepts using concept mapping performed significantly better (p < .01) than subjects who were taught using the lecture method. The concept map was also used to gain insights into the knowledge organization of high achievers and low-achievers through quantitative content analysis of their concept maps.